2023
DOI: 10.3390/ijms241512314
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Molecular Pathways in the Design of Smart Hydrogels for the Design of Vascularized Engineered Tissues

Aldo Nicosia,
Monica Salamone,
Salvatore Costa
et al.

Abstract: Biomaterials are pivotal in supporting and guiding vascularization for therapeutic applications. To design effective, bioactive biomaterials, understanding the cellular and molecular processes involved in angiogenesis and vasculogenesis is crucial. Biomaterial platforms can replicate the interactions between cells, the ECM, and the signaling molecules that trigger blood vessel formation. Hydrogels, with their soft and hydrated properties resembling natural tissues, are widely utilized; particularly synthetic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 216 publications
0
1
0
Order By: Relevance
“…Biodegradable polymers have many developing different applications in the medical field [1][2][3][4]. In recent years, research on environmentally friendly polymeric designs for biomaterials has become increasingly widespread around the world [5][6][7][8]. For instance, it has been reported that an L-lysine-loaded poly(lactic-co-glycolic acid) (PLGA) microparticle system, which supports cell proliferation and angiogenesis, has been developed as a nontoxic, biocompatible, and cost-effective microparticle system for rapid vascularization [9].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers have many developing different applications in the medical field [1][2][3][4]. In recent years, research on environmentally friendly polymeric designs for biomaterials has become increasingly widespread around the world [5][6][7][8]. For instance, it has been reported that an L-lysine-loaded poly(lactic-co-glycolic acid) (PLGA) microparticle system, which supports cell proliferation and angiogenesis, has been developed as a nontoxic, biocompatible, and cost-effective microparticle system for rapid vascularization [9].…”
Section: Introductionmentioning
confidence: 99%